Analisis Al-Qur'an Surah Al-Isra' Ayat 32 "Larangan Zina" Terhadap Fenomena Pacaran Muslimah Remaja di Era Modern - Anisa, Anisa; Hamzah, Nur; Luqman, Luqman (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research examines the prohibition of approaching adultery in the perspective of the Qur'an, especially in Surah Al-Isra' verse 32, and its relevance to the phenomenon of dating among Muslim teenagers in the modern era. The main focus of this research is an in-depth analysis of the linguistic and thematic meaning of the verse, as well as its implications for contemporary social life. The methodology used is a tafsir analysis of various prominent mufassirs such as Quraish Shihab, Hamka, Ibn Kathir, and the compiler of Tafsir Jalalain. The results show that the prohibition of approaching adultery does not only cover the act of adultery itself, but also any behavior that can lead to it, including the phenomenon of dating that is not in accordance with the Sharia. This research also reveals the significant impact of dating on the moral, psychological, and social aspects of Muslim teenagers. As a solution, this study offers a comprehensive approach through Islamic education, the active role of family and society, and Islamic alternatives such as ta'aruf in getting to know potential partners.